Emerging roles of the myocardin family of proteins in lipid and glucose metabolism. (10th May 2016) - Swärd, Karl; Stenkula, Karin G; Rippe, Catarina; Alajbegovic, Azra; Gomez, Maria F.; Albinsson, Sebastian
Abstract : This review highlights newly discovered roles of myocardin‐related transcription factors (MKL) in lipid and glucose metabolism as well as novel insights into their well‐established role as mediators of stretch‐dependent effects in smooth muscle. As a co‐factor for serum response factor (SRF), MKL regulates transcription of genes involved in the contractile function of smooth muscle cells. In addition to mechanical stimuli, this regulation has now been found to be promoted by extracellular glucose levels in smooth muscle. Recent reports also suggest that MKL can regulate a subset of genes involved in the formation of lipid‐rich invaginations in the cell membrane called caveolae. Finally, a potential role of MKLs in non‐muscle cells has been discovered as they negatively influence adipocyte differentiation. Abstract: Members of the myocardin family bind to the transcription factor serum response factor (SRF) and act as coactivators controlling genes of relevance for myogenic differentiation and motile function. Binding of SRF to DNA is mediated by genetic elements called CArG boxes, found often but not exclusively in muscle and growth controlling genes. Studies aimed at defining the full spectrum of these CArG elements in the genome (i.e. the CArGome) have in recent years, unveiled unexpected roles of the myocardin family proteins in lipid and glucose homeostasis. This coactivator family includes the protein myocardin (MYOCD), the myocardin‐related transcription factors A and B (MRTF‐A/MKL1 and MRTF‐B/MKL2) and MASTR (MAMSTR). Here we discuss growing evidence that SRF‐driven transcription is controlled by extracellular glucose through activation of the Rho‐kinase pathway and actin polymerization. We also describe data showing that adipogenesis is influenced by MLK activity through actions upstream of peroxisome proliferator‐activated receptor γ with consequences for whole body fat mass and insulin sensitivity. The recently demonstrated involvement of myocardin coactivators in the biogenesis of caveolae, Ω‐shaped membrane invaginations of importance for lipid and glucose metabolism, is finally discussed. These novel roles of myocardin proteins may open the way for new unexplored strategies to combat metabolic diseases such as diabetes, which, at the current incidence, is expected to reach 333 million people worldwide by 2025. This review highlights newly discovered roles of myocardin‐related transcription factors in lipid and glucose metabolism as well as novel insights into their well‐established role as mediators of stretch‐dependent effects in smooth muscle. As co‐factors for serum response factor (SRF), MKLs regulates transcription of genes involved in the contractile function of smooth muscle cells. In addition to mechanical stimuli, this regulation has now been found to be promoted by extracellular glucose levels in smooth muscle. Recent reports also suggest that MKLs can regulate a subset of genes involved in the formation of lipid‐rich invaginations in the cell membrane called caveolae. Finally, a potential role of MKLs in non‐muscle cells has been discovered as they negatively influence adipocyte differentiation.